Techniques and applications of digital watermarking and content protection - Arnold, Michael (Michael Konrad), 1964- (Artech House, 2003)
This unique easy-to-use software is an integration of tools and simulators that help you solve the most common feedforward predistorted amplifier design equations, including calculating gain and loop balance, optimum coupling ratios, and more. It includes the tools you need everyday, such as a microstrip calculator and parallel coupler designer, to relieve you of lengthy calculations and help you predict the performance of a complex amplifier before all the blocks are together.
Keywords: Computer security.; Digital watermarking.; Data protection.; Computer Security; Sécurité informatique.; Tatouage numérique.; Protection de l'information (Informatique); digital watermarking.; COMPUTERS -- Internet -- Security.; COMPUTERS -- Networking -- Security.; COMPUTERS -- Security -- General.; Computer security; Data protection; Digital watermarking